Coping with the crises in the periphery: The social and political costs of dollarization in Georgia - Ia Eradze (economic sociology. perspectives and conversations, 2024)
The US dollar has been an integral part of everyday life and political-economic order in Georgia for more than three decades. Thinking and planning in two currencies - the Georgian lari and the dollar - is common not only for local companies and the government but also for households. The dollar hegemony in Georgia is manifested in its high share in the currency composition of loans (45%) and deposits (51%), as well as in prices. From real estate companies to private tutors, prices are set and payments are made in US dollar, even though the only legal tender is the national currency, the lari.
Keywords: 300